2007
DOI: 10.1103/physrevlett.98.197201
|View full text |Cite
|
Sign up to set email alerts
|

Angle-DependentNi2+X-Ray Magnetic Linear Dichroism: Interfacial Coupling Revisited

Abstract: Using x ray magnetic linear dichroism (XMLD) for magnetometry requires detailed knowledge of its dependence on the relative orientation of polarization, magnetic moments, and crystallographic axes. We show that Ni 2+ L 2,3 XMLD in cubic lattices has to be described as linear combination of two fundamental spectra − not one as previously assumed. The spectra are calculated using atomic multiplet theory and the angular dependence is derived from crystal field symmetry. Applying our results to Co/NiO(001) interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
75
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 22 publications
8
75
0
Order By: Relevance
“…Experimental and theoretical studies in the last decade [5,20,21,22,23,24,25] have demonstrated that MLD-XAS is a very powerful method to investigate thin film magnetic properties, especially as far as antiferromagnetic materials are concerned. To illustrate the application of this technique specifically for our case, we start with the XAS spectra for a 30 ML NiO/Ag film.…”
mentioning
confidence: 99%
“…Experimental and theoretical studies in the last decade [5,20,21,22,23,24,25] have demonstrated that MLD-XAS is a very powerful method to investigate thin film magnetic properties, especially as far as antiferromagnetic materials are concerned. To illustrate the application of this technique specifically for our case, we start with the XAS spectra for a 30 ML NiO/Ag film.…”
mentioning
confidence: 99%
“…In contrast, 3d systems with strong CEF interaction can quite often have I 0 + I 45 ≈ 0 [7,8]. This necessitates an interesting change in the spectral shape when going from weak to strong CEF interaction, since one would unlikely encounter that the XMLD signal disappears for intermediate CEF.…”
mentioning
confidence: 99%
“…Large anisotropic x-ray magnetic linear dichroism (AXMLD) at the L 2,3 x-ray absorption (XA) edge has been reported from 3d transition metal oxides [6][7][8]. It was shown that the angular dependence of the x-ray magnetic linear dichroism (XMLD) does not only depend on the orientations of the linear x-ray polarization, E, and the sample magnetization, H, but also on the relative orientation of these two vectors with respect to the crystallographic axes.…”
mentioning
confidence: 99%
“…The element-, site-, and valence-specificity of soft x ray dichroism techniques [6] allow a thorough characterization of magnetic interfaces elucidating the basic principles of magnetic coupling. Taking into account the recently discovered strong angular dependence of XMLD [7] we find that the Co moments are oriented perpendicular to the NiO moments. We emphasize the importance of the XMLD anisotropy on the intensity ratio of the two peaks at the Ni L 2 edge, that are often used to determine the spin orientation in antiferromagnets using XMLD [8][9][10].…”
mentioning
confidence: 99%